Tradisi Mambukak Kapalo Banda dalam Kajian Living Qur’an - Elsi Novita Sari; Risman Bustamam (IAIN Batusangkar, 2021)
Living Qur'an is focused to study to see and understand the traditions that exist in society that make the Qur'an an important instrument in its implementation. The purpose of this study was to find out about the history, implementation process and also the wisdom behind this Mambukak Kapalo Banda Tradition event. The research method used is a qualitative method, with the type of case study research. Where this case study is a series of scientific activities carried out intensively, in detail and in depth about a program, event and activity either at the individual or group level to gain in-depth knowledge about the event. The results of this study indicate that the Mambukak Kapalo Banda tradition has existed since ancient times. The initial year of implementation is not known for sure, but it ranges from 1730-1930. This tradition has several processions in its implementation, starting from: slaughtering buffalo in the morning, Ratik-ratik, eating together, and finally closing with an announcement by the jorong apparatus regarding the start of planting seeds. Furthermore, the wisdom of this tradition is to strengthen the ties of friendship, to mark the start of calculating zakat, as well as to know the family tree and the distribution of high heirlooms